Practical Reporting with Ruby and Rails - Berube, David (Apress : Imprint: Apress, 2008)
Business intelligence and real-time reporting mechanisms play a major role in any of today's forward-looking business plans. With many of these solutions being moved to the Web, the popular Rails framework and its underlying Ruby language are playing a major role alongside web services in building the reporting solutions of tomorrow. Practical Reporting with Ruby and Rails is the first book to comprehensively introduce this popular framework, guiding readers through a wide-ranging array of features. Note this isn't a staid guide to generating traditional reports, but rather it shows you how the Ruby language and Rails framework can create truly compelling reporting services by plugging into popular third-party applications and services such as Google AdWords, UPS.com, iTunes, and SalesForce.com.